Utilization of Bamboo Biochar and Phonska Fertilizer on Cultivation of Maize (Zea mays L.) - Petrus Malo Ngongo; Yohanes Parlindungan Situmeang; Luh Kartini (SEAS (Sustainable Environment Agricultural Science), 2018)
This study aims to investigate the effect of biochar and phonska as well as its interaction on the growth and yield of corn crops. This experiment used a randomized block design (RBD), a factorial pattern with 2 factors. The first factor was the biochar dose consisting of 4 levels, ie: without biochar, 5 t ha-1, 10 t ha-1, and 15 t ha-1. The second factor was the dose of phonska fertilizer consisting of 2 levels: without phonska and 300 kg ha-1. The results showed that the dose of biochar 10 t ha-1 gave the highest dry weight of seed per hectare of 8.12 tons, an increase of 32.77% compared with without biochar of 6.12 tons. The treatment of phonska fertilizer dosage of 300 kg ha-1 gave the highest dry weight of seed per hectare of 8.07 tons and the increase of 26.68% compared with without phonska of 6.37 tons. Based on a result of regression analysis test obtained optimum dose 10.44 t ha-1 with a dry weight of seed per ha maximum 7.90 ton. Keywords: charcoal, bamboo biochar, NPK phonska, corn